2016
DOI: 10.1093/ofid/ofw230
|View full text |Cite
|
Sign up to set email alerts
|

Use of Nucleic Acid Amplification Tests in Tuberculosis Patients in California, 2010–2013

Abstract: Background.Nucleic acid amplification tests (NAATs) have been used as a diagnostic tool for tuberculosis (TB) in the United States for many years. We sought to assess NAAT use in TB patients in California during a period of time when NAAT availability increased throughout the world.Methods.We conducted a retrospective review of surveillance data from 6051 patients with culture-confirmed pulmonary TB who were reported to the California TB registry during 2010–2013.Results.Only 2336 of 6051 (39%) TB patients had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Today, diagnostic decisions on both drug-susceptible (DS-TB) and rifampicin (RMP) resistant TB (RR-TB) can be made within 2 h of sample collection, thus significantly reducing the lag time for diagnosis and facilitating prompt clinical decision making, which benefits TB control. 4,5 Following the World Health Organization's (WHO's) endorsement of Xpert, many countries, including Nigeria, embraced this technology with optimism. 6 It is the first simple TB molecular test that is robust enough to be introduced outside conventional laboratory settings.…”
mentioning
confidence: 99%
“…Today, diagnostic decisions on both drug-susceptible (DS-TB) and rifampicin (RMP) resistant TB (RR-TB) can be made within 2 h of sample collection, thus significantly reducing the lag time for diagnosis and facilitating prompt clinical decision making, which benefits TB control. 4,5 Following the World Health Organization's (WHO's) endorsement of Xpert, many countries, including Nigeria, embraced this technology with optimism. 6 It is the first simple TB molecular test that is robust enough to be introduced outside conventional laboratory settings.…”
mentioning
confidence: 99%
“…Theoretically, NAATs can shorten the time taken to initiate treatments in patients with PTB. Several studies using different definitions of the starting time reported a reduced time to treatment initiation [11, 12]. Utilization of NAAT(Gen-Probe) has shown an impact on treatment decisions in California, USA [11]; the median time from specimen collection to initiation of TB treatments was shorter (3 days vs 14 days) with the use of NAAT (Gen-Probe).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies using different definitions of the starting time reported a reduced time to treatment initiation [11, 12]. Utilization of NAAT(Gen-Probe) has shown an impact on treatment decisions in California, USA [11]; the median time from specimen collection to initiation of TB treatments was shorter (3 days vs 14 days) with the use of NAAT (Gen-Probe). With regard to multidrug-resistant tuberculosis (MDRTB), a retrospective study in India has reported that the use of NAAT(Hain) reduced the median time from identification of patients suspected to have MDRTB to initiation of treatments from 157 days to 38 days [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1995, nucleic acid amplification tests (NAATs) were initially approved to be performed on respiratory specimens from patients with smear-positive AFB and clinical features of tuberculosis (TB). Nucleic acid amplification test sensitivity and specificity in diagnosing MTB has been reported to be as high as 99% and 98%, respectively [ 4 , 5 ], resulting in a higher MTB detection rate and shorter time to treatment initiation [ 6 ]. Nucleic acid amplification tests of respiratory specimens from patients with suspected pulmonary TB has been recommended by the US Centers for Disease Control and Prevention (CDC) [ 7 ].…”
mentioning
confidence: 99%